2017
DOI: 10.4102/sajhivmed.v18i1.691
|View full text |Cite
|
Sign up to set email alerts
|

Non-disclosure of HIV-positive status to a partner and mother-to-child transmission of HIV: Evidence from a case–control study conducted in a rural county in Kenya

Abstract: BackgroundMany factors contribute to an enhanced risk of infant HIV acquisition, two of which may include failure of a mother to disclose her HIV-positive status to her partner and exclusion of male partners in preventing mother-to-child transmission of HIV (PMTCT) interventions. To justify why HIV programmes need to integrate male partner involvement and partner disclosure, we need to establish an association between the two factors and infant HIV acquisition.ObjectiveTo determine whether failure to disclose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
0
10
1
Order By: Relevance
“…Besides, discussion of hitherto private social problems might have helped women address other social problems they were struggling with. For example, other research findings highlight how disclosure of HIV status and lack of partner's support may inhibit access to PMTCT services (32). Similarly, the findings from this study can provide insights into the use of digital technology in the provision of health services.…”
Section: Discussionmentioning
confidence: 69%
“…Besides, discussion of hitherto private social problems might have helped women address other social problems they were struggling with. For example, other research findings highlight how disclosure of HIV status and lack of partner's support may inhibit access to PMTCT services (32). Similarly, the findings from this study can provide insights into the use of digital technology in the provision of health services.…”
Section: Discussionmentioning
confidence: 69%
“…The overall rate of disclosure is in line with study conducted in Uganda in that 83.8% had disclosed their sero-status to at least one person, 22 study of South Africa (80.0%) disclosed to one of their family 23 and Kenyan study (83%). 24 However it is higher than the rate (59%) found in a study conducted in South African HIV positive pregnant women. 2 Still much higher than in Tanzania (60%) of those pregnant women interviewed had disclosed to significant others.…”
Section: Discussionmentioning
confidence: 69%
“…7 Qualitative studies show that PWLHIV fear being seen taking medications or attending PMTCT services 8,9 The detrimental consequences of non-disclosure during pregnancy are well documented: lack of disclosure contributes to 9.8 times higher odds of infant HIV acquisition, ART non-adherence for both the mother and infant, and 2.8 times higher likelihood of loss to follow up from ART care. [10][11][12] A case-control study found that mothers living with HIV who had uninfected infants were 14 times more likely to have disclosed their status to their male partners than mothers with HIV-infected infants. 13 Similarly, a national survey in Kenya found that non-disclosure during pregnancy was associated with 12.8 times higher odds of MTCT of HIV.…”
Section: Background and Significancementioning
confidence: 99%